Efficacy of dietary supplementation with 1α-hydroxycholecalciferol on performance, eggshell quality, serum metabolites, jejunal morphology and bone characteristics of laying hens at the late stage of production - Maryam Ghaderi Nik; Reza Mahdavi; Shahab Ghazi; Kourosh Gholami (Poultry Science)
The present study evaluated the effects of 1α-hydroxycholecalciferol (1αOHD3) supplementation on performance, egg quality, gut morphology, serum metabolites, and bone characteristics of Lohman LSL-Lite laying hens. A total of 180 birds (110 weeks of age) were allocated according to a completely randomized design with five treatments. Each treatment had six replicates containing six hens each. The treatments consisted of basal diet with 2000 IU/kg vitamin D3, basal diet supplemented with 1.5, 3, 4.5, and 6 μg/kg of 1αOHD3. Results showed that dietary supplementation with 1αOHD3 increased the egg production (linear P = 0.002 and quadratic P = 0.009) and gross revenue (linear P = 0.042) whilst it decreased the abnormal eggs (linear P = 0.004 and quadratic P = 0.009) in aged laying hens. Similarly, it linearly and quadratically increased the shell thickness and eggshell strength (P < 0.001). Egg mass (linear P = 0.075) showed a tendency to increase with increasing dietary 1αOHD3 supplementation levels. The egg quality parameters, including Haugh unit, relative weight of albumen, yolk and eggshell were not affected by the treatments (P > 0.05). Furthermore, 1αOHD3 supplementation increased the serum levels of calcium (linear P = 0.003 and quadratic P = 0.011), albumin (linear P = 0.016 and quadratic P = 0.033), vitamin D (linear and quadratic P < 0.001), alanine aminotransferase activity (linear P = 0.02) whilst the addition of 1αOHD3 decreased alkaline phosphatase activity (linear P = 0.003 and quadratic P = 0.011), without affecting the serum levels of phosphorus and aspartate aminotransferase activity (P > 0.05) in laying hens. In addition, the linear tendency to increase was observed (linear P = 0.062) in total protein. Dietary supplementation of 1αOHD3 increased the tibia diameter (linear P = 0.053), tibia calcium (linear P = 0.004 and quadratic P = 0.014) and tibia strength (linear and quadratic P < 0.001). The addition of 1αOHD3 did not affect the phosphorus and ash of the tibia (P > 0.05). Linear and quadratic responses were found for crypt depth (linear and quadratic P = 0.001) and villus height to crypt depth ratio (linear P = 0.004 and quadratic P = 0.010). The experimental treatments did not affect the jejunal villus height, villus width and villus surface area in aged laying hens (P > 0.05). Our findings suggest that the inclusion of 1αOHD3 is beneficial, as it enhances egg production, profitability, eggshell thickness, and tibia quality while reducing the incidence of abnormal eggs during the later phase of egg production.